Minang Women’s Music in Matrilineal Kinship: Revealing the Boundaries of Ethics and Performance Aesthetics - Sriwulan, Wilma; Irwan, Irwan; Kasman, Selvi; Hendri, Yon; Erizal, Erizal (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2023)
This research aims to reveal Minang women’s music to find a common thread perspective on Minangkabau matrilineal women. The method used in this research is a women’s perspective research method (feminist perspective). This method produces a very distinctive report, which is obtained from data through feminist ethnography, which is a report on the results of field research. The findings are that women’s music based on Adat Salingka Nagari is a women’s music that blends with Adat (tradition) and provides an opportunity to actualize themselves in the societies; as a result of being a Anak Dendang they get more than enough benefits and as family breadwinners.